Finite Element Simulation and Experimental Verification of Tightness the Transmission Joint Surface - Chen Yun; Liu Shidao (Jixie chuandong)
Against the phenomenon that oil leakage at joint of one longitudinal transmission is fed back from market,firstly,the finite element method is applied to analyze the static gap of joint surface of housing.Secondly,considering the working conditions of first gear and reverse gear,the dynamic gap of the joint surface of housing is analyzed,and a surface pressure test against the housing is carried out,the correctness of theoretical analysis is verified,meanwhile it is found that the oil leakage is caused by the quality of the joint surface of the housing. At last,simulating the reality of transmission producing,the joint surface is coated with sealant before making a surface pressure test which shows that the joint surface has uniform pressure and reliable seal,and the theory design is proved to be free of problems,a reference for the study of the tightness of transmission housing joint surface is provided.